Social Dynamics and Interfaith Tolerance: A Case Study of the MUI Fatwa on the Belief System of the Dayak Hindu-Buddha Bumi Segandu in Losarang, Indramayu - Bisri, Bisri; Kirom, Syahrul; Permana, Muhamad Adam (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2025)
Purpose- This study aims to examine the role of the Nahdlatul Ulama Regional Board (PCNU) of Indramayu in promoting interfaith tolerance and maintaining religious harmony following the issuance of a fatwa by the Majelis Ulama Indonesia (MUI), which labeled the beliefs of the Segandu Hindu-Buddhist Dayak community as deviant. Design/methods/approach- Using a qualitative research design, the study collects data through interviews, observation, and documentation. The data are then analyzed thematically to uncover patterns in the response and engagement of PCNU Indramayu. Findings- The findings reveal that PCNU Indramayu acts as a mediator to reduce social tensions by advocating the values of ukhuwah (brotherhood) and wasathiyyah (moderation). Through public education and community engagement, the organization fosters tolerance and encourages mutual respect among religious groups, mitigating the risk of discrimination and conflict. Research Implications- This research highlights the importance of civil Islamic organizations in conflict resolution and religious peacebuilding. It offers a model for how local religious actors can counteract intolerance and support pluralism in a religiously diverse society.